The Components of Talent: Company Size and Financial Centres in the European Investment Management Industry. Issue 1 (2nd January 2016) - Clark, Gordon L.
Abstract : Clark G. L. The components of talent: company size and financial centres in the European investment management industry, Regional Studies . As the centre for advanced financial services, and having the complex array of services needed to invest beyond Europe's borders, London dominates the European financial services industry. As in other global financial centres there is a premium on talented investment managers, identified in the media as 'star performers'. Investment companies rely on such employees for risk-adjusted rates of return on the basis of asset- and/or style-specific investment strategies while protecting their clients against the risks occasioned by market uncertainty. Drawing upon frameworks from organizational ecology, this paper integrates the size of companies with the market for talent sectorally and geographically.